The use of parallel imaging for MRI assessment of knees in children and adolescents. - Doria AS; Chaudry GA; Nasui C; Rayner T; Wang C; Moineddin R; Babyn PS; White LM; Sussman MS; Doria, Andrea S; Chaudry, Gulraiz A; Nasui, Cristina; et al. (Pediatric Radiology, 2010)
Background: Parallel imaging provides faster scanning at the cost of reduced signal-to-noise ratio (SNR) and increased artifacts.Objective: To compare the diagnostic performance of two parallel MRI protocols (PPs) for assessment of pathologic knees using an 8-channel knee coil (reference standard, conventional protocol [CP]) and to characterize the SNR losses associated with parallel imaging.Materials and Methods: Two radiologists blindly interpreted 1.5 Tesla knee MRI images in 21 children (mean 13 years, range 9-18 years) with clinical indications for an MRI scan. Sagittal proton density, T2-W fat-saturated FSE, axial T2-W fat-saturated FSE, and coronal T1-W (NEX of 1,1,1) images were obtained with both CP and PP. Images were read for soft tissue and osteochondral findings.Results: There was a 75% decrease in acquisition time using PP in comparison to CP. The CP and PP protocols fell within excellent or upper limits of substantial agreement: CP, kappa coefficient, 0.81 (95% CIs, 0.73-0.89); PP, 0.80-0.81 (0.73-0.89). The sensitivity of the two PPs was similar for assessment of soft (0.98-1.00) and osteochondral (0.89-0.94) tissues. Phantom data indicated an SNR of 1.67, 1.6, and 1.51 (axial, sagittal and coronal planes) between CP and PP scans.Conclusion: Parallel MRI provides a reliable assessment for pediatric knees in a significantly reduced scan time without affecting the diagnostic performance of MRI.